How external inputs can maintain Pacific island soil fertility - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Agriculture is the main base of the economy of the South Pacific islands, and a subsistence system of mixed cropping, starchy root crops mixed with banana, breadfruit and coconut, is the mainstay. Farmers use a variety of local resources to...